The Use of Precision‐Cut Lung Slices for Studying Innate Immunity to Viral Infections. Issue 8 (8th August 2022) - Michalaki, Christina; Dean, Charlotte; Johansson, Cecilia
Abstract: Precision‐cut lung slices (PCLS) are a novel tool to study cells of the lower airways. As PCLS retain the integrity and architecture of the lung, they constitute a robust model for studying the cells of the lower respiratory tract. Use of PCLS for imaging has been previously documented; however, other applications and techniques can also be applied to PCLS to increase their use and therefore decrease the number of animals needed for each experiment. We present a detailed protocol for generating PCLS from the murine lung. We show that cultured PCLS remain viable up to at least 8 days of culture, that RNA can be isolated from the tissue, and that flow cytometry can be carried out on the cells obtained from the PCLS. Furthermore, we demonstrate that cytokines and chemokines can be detected in the culture supernatants of PCLS exposed to viruses. Overall, these protocols expand the use of PCLS, especially for infection studies. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Precision‐cut lung slices (PCLS) Basic Protocol 2 : PCLS culture and viability Basic Protocol 3 : RNA isolation from PCLS, cDNA conversion, and RT‐qPCR Basic Protocol 4 : Staining of cells from PCLS for flow cytometry Basic Protocol 5 : In vivo RSV administration and ex vivo PCLS RSV exposure